2020
DOI: 10.1371/journal.pone.0227235
|View full text |Cite
|
Sign up to set email alerts
|

Color discrimination and gas chromatography-mass spectrometry fingerprint based on chemometrics analysis for the quality evaluation of Schizonepetae Spica

Abstract: Schizonepetae Spica (SS), the dried spike of Schizonepeta tenuifolia Briq., is a traditional Chinese medicinal herb. According to the color of persistent calyx, SS is categorized into two classes: the yellowish-green-type and the brownish-type. Based on the chemometrics analysis of gas chromatography-mass spectrometry (GC-MS), a novel model of identifying and evaluating the quality of SS in different colors was constructed for the first time in this work. 20 batches SS samples of different colors were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The number of identified peaks in SS and SSC were 39 and 62, accounting for 93.90% and 74.56% of their total volatile content, respectively. The main volatile constituents (>1%) of SS included V18 ( l -menthone, 13.05%), V19 (menthofuran, 3.18%), V20 ( trans -5-methyl-2-(1-methylvinyl)cyclohexan-1-one, 2.84%), V25 (2-allyl-4-methylphenol, 1.11%), V26 (pulegone, 58.70%), V37 (3-methyl-6-(1-methylethylidene)cyclohex-2-en-1-one, 3.21%), V48 (caryophyllene, 1.28%) and V83 (linolenic acid, 2.67%), a result that was in accordance with the findings of recent studies [ 27 , 28 ]. The volatile composition and relative contents of SS notably changed after processing by stir-frying, as V18 ( l -menthone, 1.84%), V19 (menthofuran, 1.46%), V20 ( trans -5-methyl-2-(1-methylvinyl)cyclohexan-1-one, 1.75%), V26 (pulegone, 27.44%), V35 (2,5,6-trimethylbenzimidazole, 1.01%), V61 (caryophyllene oxide, 1.40%), V72 (3,7,11-trimethyl-1-dodecanol, 1.49%), V73 (neophytadiene, 10.11%), V75 (phytol acetate, 1.58%), V77 (3,7,11,15-tetramethyl-2-hexadecen-1-ol, 3.95%), V80 (methyl palmitate, 1.56%) and V82 (methyl linolenate, 1.28%) were determined to be the main volatile constituents of SSC.…”
Section: Resultssupporting
confidence: 92%
“…The number of identified peaks in SS and SSC were 39 and 62, accounting for 93.90% and 74.56% of their total volatile content, respectively. The main volatile constituents (>1%) of SS included V18 ( l -menthone, 13.05%), V19 (menthofuran, 3.18%), V20 ( trans -5-methyl-2-(1-methylvinyl)cyclohexan-1-one, 2.84%), V25 (2-allyl-4-methylphenol, 1.11%), V26 (pulegone, 58.70%), V37 (3-methyl-6-(1-methylethylidene)cyclohex-2-en-1-one, 3.21%), V48 (caryophyllene, 1.28%) and V83 (linolenic acid, 2.67%), a result that was in accordance with the findings of recent studies [ 27 , 28 ]. The volatile composition and relative contents of SS notably changed after processing by stir-frying, as V18 ( l -menthone, 1.84%), V19 (menthofuran, 1.46%), V20 ( trans -5-methyl-2-(1-methylvinyl)cyclohexan-1-one, 1.75%), V26 (pulegone, 27.44%), V35 (2,5,6-trimethylbenzimidazole, 1.01%), V61 (caryophyllene oxide, 1.40%), V72 (3,7,11-trimethyl-1-dodecanol, 1.49%), V73 (neophytadiene, 10.11%), V75 (phytol acetate, 1.58%), V77 (3,7,11,15-tetramethyl-2-hexadecen-1-ol, 3.95%), V80 (methyl palmitate, 1.56%) and V82 (methyl linolenate, 1.28%) were determined to be the main volatile constituents of SSC.…”
Section: Resultssupporting
confidence: 92%
“…Sensory indicators of color, taste, and odor are the key evaluation indexes of TCMs, which are considered to be important components and intuitive attributes in the identification of traits [ 13 , 14 , 15 ]. Ben Cao Yuan Shi, the book of Origins of the Materia Medica, emphasized the significance of color, taste, and odor as identifiers of high-quality medicinal herbs [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Natural plants, especially medicine food homology and functional foods, are increasingly used, for instance, Schizonepetae Spica , the dried flower spike of Schizonepetae Herba [ 7 , 8 ]. Traditional Chinese medicine believes that the incidence of UC is related to dampness, and it has been found that the windproof effect of Schizonepetae Herba can significantly improve the symptoms of abdominal pain, diarrhea, pus and bloody stool in patients with colitis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%